2015
DOI: 10.5371/hp.2015.27.4.250
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of Femoral Head Treated with Extracorporeal Shock Wave Therapy: Analysis of Short-term Clinical Outcomes of Treatment with Radiologic Staging

Abstract: PurposeTo evaluate clinical results of extracorporeal shock wave therapy (ESWT) with radiographic staging on patients with avascular necrosis of femoral head (AVNFH).Materials and MethodsWe evaluated 24 patients diagnosed with AVNFH (32 hip joints) who were treated with ESWT from 1993 to 2012. Average follow-up period was 27 months, and the average age of patients was 47.8 years. The Association Research Circulation Osseous (ARCO) system was used to grade radiographic stage prior to treatment. For this study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…It must be pointed out that in this study they did not undertake MRI examination and the definition of cure was disappearance of clinical symptoms. In 2012, Vulpiani et al [23] [29] also divided patients on the basis of ARCO stage and obtained similar results. Kusz et al [24] demonstrated considerable enhancement of quality of life in ONFH patients after ESWT; however, they only followed up patients for 6 weeks.…”
Section: Therapeutic Effect Of Eswt For Onfhmentioning
confidence: 84%
See 4 more Smart Citations
“…It must be pointed out that in this study they did not undertake MRI examination and the definition of cure was disappearance of clinical symptoms. In 2012, Vulpiani et al [23] [29] also divided patients on the basis of ARCO stage and obtained similar results. Kusz et al [24] demonstrated considerable enhancement of quality of life in ONFH patients after ESWT; however, they only followed up patients for 6 weeks.…”
Section: Therapeutic Effect Of Eswt For Onfhmentioning
confidence: 84%
“…Eventually, 17 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] studies were considered to be eligible for this systematic review, 16 [13][14][15][16][17][18][19][20][21][23][24][25][26][27][28][29] of which were published in English and only 1 [22] was published in Chinese. Next, we extracted 3 types of useful data from included studies and imported them into different tables: basic information of included publications ( Table 1); technological details of extracorporeal shockwave therapy ( Table 2) and therapeutic effect assessment indexes of included studies ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations